2020
DOI: 10.1155/2020/3431597
|View full text |Cite
|
Sign up to set email alerts
|

The Crosstalk between Calcium Ions and Aldosterone Contributes to Inflammation, Apoptosis, and Calcification of VSMC via the AIF-1/NF-κB Pathway in Uremia

Abstract: Vascular calcification is a major complication of maintenance hemodialysis patients. Studies have confirmed that calcification mainly occurs in the vascular smooth muscle cells (VSMC) of the vascular media. However, the exact pathogenesis of VSMC calcification is still unknown. This study shows that the crosstalk between calcium and aldosterone via the allograft inflammatory factor 1 (AIF-1) pathway contributes to calcium homeostasis and VSMC calcification, which is a novel mechanism of vascular calcification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Previous studies aimed at addressing mechanistic insights on the protective effect of Mg on vascular cells gave relevance to the properties of Mg as a calcium antagonist, 1 so that calcium action is susceptible of being modified by the Mg supplement. A rise in the intracellular calcium can activate transduction pathways leading to an increase in oxidative stress, the activation of the NF‐κB signalling and the production of pro‐inflammatory cytokines 49,50 . Thus, as a physiological inhibitor of calcium channels, Mg might prevent calcium flux and therefore the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies aimed at addressing mechanistic insights on the protective effect of Mg on vascular cells gave relevance to the properties of Mg as a calcium antagonist, 1 so that calcium action is susceptible of being modified by the Mg supplement. A rise in the intracellular calcium can activate transduction pathways leading to an increase in oxidative stress, the activation of the NF‐κB signalling and the production of pro‐inflammatory cytokines 49,50 . Thus, as a physiological inhibitor of calcium channels, Mg might prevent calcium flux and therefore the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, IL-1β contributes to senescence-associated calcification through the NF-κB/p53/p21 signaling pathway [ 25 , 144 ]. Moreover, oxidative stress products from SASP impel VC processes and CKD progression by activating the renin-angiotensin system, TGF-β, and Wnt/β-catenin signal pathways, consequently accelerating kidney fibrosis and ESRD [ 68 , 145 , 146 ].…”
Section: Aging Aggravates Vc Attrition In Patients With Progressive Ckdmentioning
confidence: 99%
“…Activated macrophages are known to promote the proliferation and migration of SMCs. 42,43 The transwell migration assay results (Figure 5f,h) showed that the proliferation and migration abilities of SMCs decreased sharply after PTT or PDT treatment, especially for the sequential PTT/PDT combined treatment, due to the efficient ablation of activated macrophages. The PTT/PDT effects of CS-CNCs@ Ce6/DS on unactivated macrophages were also explored.…”
Section: 4mentioning
confidence: 99%